e+18=45

Simple and best practice solution for e+18=45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for e+18=45 equation:


Simplifying
e + 18 = 45

Reorder the terms:
18 + e = 45

Solving
18 + e = 45

Solving for variable 'e'.

Move all terms containing e to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + e = 45 + -18

Combine like terms: 18 + -18 = 0
0 + e = 45 + -18
e = 45 + -18

Combine like terms: 45 + -18 = 27
e = 27

Simplifying
e = 27

See similar equations:

| xyz=20 | | 51=-9x-6 | | -3(n-8)=28-7n | | Y=(30-2x)(40-2x)(x) | | 4x-6x+12=20 | | 1307.2=17.2a | | 5-3x=19+4x | | 30-5v+2v=3v-12 | | 4n-12=11-4n | | 15x+8y=131 | | -131=-3-4(8-3v) | | a-20=17 | | -3m+4=-2m-5 | | 12=10y-8y | | x-7=3(x-4) | | 6-x=3(x+10) | | 10b+8b=360 | | 3075=37.5a | | 6x^2+36x+192=0 | | 5x-12=9x+5 | | 3(x+2)+1=2x-8+x+13 | | -16=2a-6a | | 637=13a | | x^2=-2+15 | | 5z=1.7+4.3 | | f(x)=6x^2+36x+192 | | x+37=129 | | 4+(m/5)=6 | | -5n-8-56m=-8 | | 4x^2+9=2x^2+3(5x+3) | | (2x^2)-(1x)-24=0 | | 12h^2-31h+20= |

Equations solver categories